ANALISIS POTENSI PENGEMBANGAN TERNAK SAPI POTONG DI KABUPATEN BANYUMAS - Nida Amaniyya Ali; Nunung Noor Hidayat; Pambudi Yuwono (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The purpose of the study were 1. To know the population of beef cattle and ruminant of each sub-district in Banyumas Regency; 2. To know the trend of beef cattle population from 2014 to 2019 in Banyumas Regency; 3. To analyze the development potential of beef cattle in Banyumas Regency based on the LQ index; 4. To know the potential development of beef cattle in Banyumas Regency based on the potential of climatology. Materials and Methods. The study used secondary data as primary data, secondary data were obatined from official government websites from 2014 to 2019. The data analysis were population trend analysis, and LQ analysis which were then described descriptively. Results. The results showed that the cattle population of cattle experienced a very small increase. The base areas of cattle development based on LQ > 1 index were: Kembaran, Sokaraja, Kalibagor, Sumbang, Kedung banteng, Baturraden, Jatilawang, and Cilongok. Conclusion. The environmental temperature and rainfall of Banyumas Regency were ideal for the development of beef cattle.